The Relationship between Working Memory and Acquisition of Mathematical Strategies in Children with Cerebral Palsy: A Review of Literature - Sanaz Tajadini; Hamid Reza Farpour; Sima Farpour (Shiraz University of Medical Sciences, 2019)
Background: Cerebral Palsy (CP) is defined as non-progressive brain damage attributed to limitation in mobility, learning, language, and communication. The high prevalence of low academic achievement in learning mathematics in CP cases is related, in part, to multifactorial influences; working memory may be one of the factors which can be related to arithmetic attainment. The purpose of this article was to review the relationship of working memory with mathematical performance in children with CP. Methods: In this Review of literature article, Five English search engines (Pubmed, Scopus, Science direct, EMBASE, and Central) were used with key words, "cerebral palsy, arithmetic, mathematical performance, and working memory". The inclusion criteria were English relevant articles in which participants had CP and both mathematical abilities and working memory were assessed. Results: A total of 103 articles were screened. Twenty-five potentially relevant titles or abstracts were identified. Based on inclusion criteria, only 7 articles were found. Conclusion: Given the high risk of mathematical learning difficulties in children with CP, information about mathematical skills and the role of working memory on the different components of mathematical strategies is limited. Further research should be carried out to investigate this issue. The findings in this study showed the relationship between working memory and the difficulties with mathematical and numerical learning of CP cases.